A comprehensive bibliometric analysis of ferroptosis in tumor resistance: development and emerging trends - Xie, Liangyun; Zhang, Yafei; Niu, Xiedong; Kang, Yuan; Li, Wenyao; Yao, Jun (Frontiers in Immunology, 2025)
BackgroundFerroptosis is a regulated form of cell death characterized by iron dependency, lipid peroxidation, and oxidative stress. Since its discovery in 2012, ferroptosis has attracted significant interest for its potential to counteract tumor resistance across various therapeutic modalities, including chemotherapy, radiotherapy, immunotherapy, and targeted therapy. Despite notable progress, a systematic understanding of its underlying molecular mechanisms and translational potential remains underdeveloped, thus necessitating a comprehensive bibliometric analysis.MethodsWe employed bibliometric tools, including VOSviewer, CiteSpace, and bibliometric.com, to analyze 2,663 articles related to ferroptosis and tumor resistance indexed in the Web of Science Core Collection from 2014 to 2024. The analysis included co-occurrence, co-citation, and clustering techniques to explore trends, influential keywords, prominent journals, leading institutions, and key contributors. Citation burst detection and temporal analysis were used to uncover emerging research hotspots and track the field’s evolution.ResultsOver the past decade, the volume of publications in this field has grown rapidly, with China and the United States leading in both research output and academic influence. Notable institutions such as Central South University and Fudan University contributed significantly, while Kang Rui and Tang Daolin emerged as prolific authors. Key research hotspots identified include oxidative stress, tumor microenvironment, and nanomedicine, with emerging themes such as immunotherapy and autophagy gaining prominence. Temporal trends indicated a shift from mechanistic studies toward translational applications, emphasizing the integration of ferroptosis in clinical strategies to address tumor resistance.ConclusionsThis bibliometric analysis highlights ferroptosis as a rapidly evolving field with significant contributions to understanding tumor resistance mechanisms. The identification of emerging themes and promising research directions offers valuable insights for future investigations and clinical applications of ferroptosis in overcoming tumor resistance.